FRAX and the effect of teriparatide on vertebral and non-vertebral fracture. Issue 11 (November 2015) - Harvey, N.; Kanis, J.; Odén, A.; Burge, R.; Mitlak, B.; Johansson, H.; McCloskey, E.
Abstract Summary Daily teriparatide injections have been shown to reduce vertebral and non-vertebral fractures. Here, we demonstrate that the magnitude of fracture risk reduction is independent of baseline fracture probability assessed by FRAX. Introduction Daily administration of 20 or 40 μg teriparatide has been shown to significantly decrease the risk of vertebral and non-vertebral fracture compared with placebo. The aim of the present study was to evaluate fracture risk assessed at baseline using the FRAX® tool and to determine the efficacy of teriparatide as a function of baseline fracture risk. Methods One thousand six hundred thirty-seven postmenopausal women in the pivotal phase three trial, randomly assigned to receive placebo (n  = 544), teriparatide 20 μg per day (n  = 541) or teriparatide 40 μg per day (n  = 552), were studied. Baseline clinical risk factors were entered into country-specific FRAX models to compute the 10-year probability of major osteoporotic fractures with or without input of femoral neck BMD. Because there was no difference in effect of 20 and 40 μg teriparatide daily on fracture occurrence, the two active groups were merged. The interaction between probability of a major fracture and treatment efficacy was examined by Poisson regression. Results The 10-year probability of major osteoporotic fractures (with BMD) ranged from 2.2–67.2 %. Treatment with teriparatide was associated with a 37 % decrease in all non-vertebral fractures (95 % CI 10–56 %) and a 56 % decrease in low-energy non-vertebral fractures (95 % CI 24–75 %) compared with placebo. The risk of morphometric vertebral fractures decreased significantly by 66 % (95 % CI 50–77 %). Hazard ratios for the effect of teriparatide on the fracture outcome did not change significantly with increasing fracture probability (p  > 0.30). Similar findings were noted for the interaction when BMD was excluded from the FRAX model, or when probability of hip fracture was used as the marker of baseline risk. Conclusion We conclude that teriparatide significantly decreases the risk of non-vertebral and morphometric vertebral fractures in women by a similar extent, irrespective of baseline fracture probability.